Effectiveness of comparative advertising in Czech Republic - Gavrilova, Polina; Machek, Martin; Průša, Přemysl, 1980-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This thesis aims to analyze the effectiveness of Direct versus Indirect comparative advertising in low and high-context communication cultures in Czech Republic. These two groups are represented by Czech consumers and Vietnamese minority. The goal is to determine potential differences in the attitude towards this marketing technique among the two culturally distinguished groups. The effectiveness of the ad was measure using two constructs: attitude towards the ad and persuasion effect. For the purpose of this study a survey was conducted among 200 consumers, in the capital of Czech Republic, Prague. Czech consumers were found to have a more positive attitude toward the direct comparative advertising than Vietnamese consumers. Further, the Vietnamese respondents showed a significantly better acceptance of indirect comparative advertising than of the direct comparative one. In addition, it was found that the age category does have a slight influence on the consumers attitude towards the comparative advertising. The recommendations from this thesis, can serve as a basis for better strategical and tactical decisions concerning the usage of comparative advertising.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses